After Alice After Cats in Derrida's L'animal que donc je suis. Issue 2 (November 2014) - Polish, Jessica
<x xml:space="preserve">Abstract</x> In this essay, I argue that Derrida cannot pursue the question of being/following unless he thinks through the question of sexual difference posed by figures of little girls in philosophical texts and in literature, specifically as posed by Lewis Carroll's Alice whom Derrida references in L'animal que donc je suis. At stake in thinking being after animals after Alice is the thought of an other than fraternal following, a way of being-with and inheriting from (other than human) others that calls for an account of development that is not dictated by a normative autotelic and sacrificial logic. I argue that Derrida's dissociation of himself and his cat from Alice and her cat(s) in L'animal que donc je suis causes him to risk repeating the closed, teleological gestures philosophers like Kant and Hegel perpetuate in their accounts of human development. The more sweeping conclusion towards which this essay points is the claim that the domestication of girls and their subjection to familial fates in narratives and the reduction of development to teleology more generally, require the sacrifice and forgetting of 'nature', including animals, so that the fates of girls and 'nature' are intertwined in the context of projects of human world-building and home-making.